THE LOCATING CHROMATIC NUMBER OF CHAIN(A,4,n) GRAPH - Welyyanti, Des; Abel, Latifa Azhar; Yulianti, Lyra (PATTIMURA UNIVERSITY, 2025)
Let be a connected graph with a vertex coloringsuch that two adjacent vertices have different colors. We denote an ordered partition where is a color class with color-, consisting of vertices given color , for . The color code of a vertex in is a -vector: . where is the distance between a vertex in and for . If every two vertices and in have different color codes, , then is called the locating -coloring of . The minimum number of colors k needed in this coloring is defined as the locating chromatic number, denoted by . This paper determines the locating chromatic number of chain graph and the induction of two graphs . Graph is a cyclic graph , which is the identification of , for n>2.